Innovative micro-NMR/MRI functionality utilizing flexible electronics and control systems - Nassar, Omar (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2023)
The advantages offered by the flexible electronics and control systems technologies were utilized for tackling the challenges facing two crucial Magnetic Resonance (MR) applications. The first application is in the field of interventional Magnetic Resonance Imaging (MRI), and the other application is in the field of Nuclear Magnetic Resonance spectroscopy (NMR).